The cultural study of Brazilian popular music: two problems and a contribution (Per Musi, 2010)
At the current state of popular music studies in Brazil, it is crucial to discuss the definition of “popular music”, and the theoretical approaches employed to ground its analysis. Both issues are examined here through a critical articulation involving musical structures, society and culture. Thus, what I propose is a theoretical contribution to Brazilian popular music studies, not an analysis of the content of such studies.